Correlation of compaction characteristics of standard and reduced Proctor tests. Issue 6 (11th December 2020) - Hirebelaguly Shivaprakash, Shaivan; Sridharan, Asuri
Abstract : Analysis of reduced Proctor test and standard Proctor test results collected from literature indicates that it is possible to replace standard Proctor with reduced Proctor due to the advantages that the reduced Proctor test requires 40% less compaction energy, requires no modifications to the standard Proctor compaction apparatus unlike other small compaction tests, and the soil particle size requirements remain the same as those for the standard Proctor test. Correlations were also developed for compaction characteristics obtained by the modified Proctor test and the reduced Proctor test in order to estimate compaction characteristics at the modified Proctor energy level by just performing the reduced Proctor test. The optimum moisture content was found to correlate well with liquid limit. In addition, for the reduced Proctor test, maximum dry density was found to have a very good correlation with optimum moisture content.